ANALISIS YURIDIS PUTUSAN PENGADILAN AGAMA TANGERANG NOMOR 1654/PDT.G/2025/PA.TNG TENTANG CERAI TALAK DENGAN KESEPAKATAN MEDIASI - Syarif Hidyatullah; Ahmad Sarmadi (EKOSSISTEM : Islamic Economics, Banking, Law, System, 2026)
The process of resolving divorce cases not only concerns the dissolution of the marital bond but also has implications for civil rights. This study analyzes the Tangerang Religious Court Decision Number 1654/Pdt.G/2025/PA.Tng, which granted a talak divorce petition based on a mediation agreement reached between the Petitioner and the Respondent regarding post-divorce rights. The research focuses on the validity of the partially successful mediation agreement, the judge's legal reasoning, and the juridical implications of incorporating this agreement into the final ruling. The research employs a normative juridical method, using a statutory approach and case analysis. The findings indicate that the judge carefully considered the formal and material requirements of the mediation agreement in accordance with Articles 1320 and 1337 of the Indonesian Civil Code (KUHPerdata), and integrated them into the operative section of the judgment. The agreement is binding on the parties and possesses executory legal force. This decision reflects the court's endeavor to resolve divorce cases comprehensively while taking into account the interests of both parties and their children.